Factors that Influence the Adoptions of Internet Banking Among Customers - Bin Haji Saman, Muhammad Azimulhakim (American Finance & Banking Review, 2018)
Internet banking is the latest technology that has revolutionized the changes of banking and business systems around the world. However, arrival of technology has an impact on Internet banking and transforms from a traditional banking system to a very useful innovation technology. The purpose of this study is to analyze factors that have influenced users to use Internet banking in doing financial transaction. This study uses content analysis on the previous literatures. The findings showed that there were 10 main different factors which influence the adoption of internet banking by the users. This study also proved that the highest factors which consist of 2 main factors are generated from technology acceptance model (TAM). Contribution of this research are significantly helps bank to have a better understanding on factors that influence the adoption of internet banking as well as help to develop a strategy to improved internet banking services.